Karakterisasi FTIR Poliblend Adsorben Serbuk Biji Buah Kelor (Moringa Oleifera) Dan Cangkang Ayam Ras Untuk Pengolahan Air Gambut Di Daerah Palu Barat - M. Yusi Prilina Bertus; Suherman Suherman; Sri Mulyani Sabang (Universitas Tadulako, 2014)
The seed of moringa (Moringa oleifera) is used as natural water purification materials and are coagulant. Biocoagulant materials combined in this study were egg shells. Egg shell is known to contain high calcium. This study aims to determine the character of polyblends in physical – chemical test, the degree of swelling an polyblends functional groups, and to determine the optimum ability of the polyblends power absorption. The research method used was sampel preparation, polyblends characterization, swelling degree and to analyze FTIR functional group and water quality test with parameters. The research results showed that the physical character polyblends lasting effectiveness was polyblends SBK : SCT with a ratio of 5:5, while the chemistry test of polyblends character with FTIR analysis showed the functional groups OH, C=C, CH, CH2, CO which each have their own unique characteristics. The water quality with parameters of turbidity, good polyblends adsorption was polyblends SBK:SCT with ratio of 7.5:2.5 with a decreased of 91.43%, ferrous metal content, polyblends SBK:SCT with a ratio of 7.5:2.5 declined 90.90%. The value test of BOD and COD, the best polyblend adsorption was polyblends 5:5 with 93.26% dcreased. Polyblends that produced the best pH of water quality was polyblend with a ratio of 7.5:2.5 with the pH value of 4.68 turned to 7.82.